2021
DOI: 10.1111/jav.02616
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and weather during moult on mountain bluebird Sialia currucoides structural colouration

Abstract: Birds exhibit a vast array of colours and ornaments and while much work has focused on understanding the function and evolution of carotenoid‐based colours (red, orange, yellow), structural colouration (blue, green, purple, iridescent) can also play a key role in sexual signaling. Several studies have examined how factors such age may influence structural colour, however few studies have looked at how structural colour may be influenced by environmental conditions such as variation in weather conditions experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Additionally, we examined whether species living in closer proximity displayed greater color divergence as a test of the species recognition hypothesis. We predicted (1) plumage of both sexes would be largely driven by migration behavior, diet, climate, and habitat because these aspects have been found to influence coloration in other groups (e.g., Reudink et al 2015, Simpson et al 2015, Ward et al 2021, and (2) we would find less support for the species recognition hypothesis because many Tyrant flycatchers exhibit similar plumage within genera but display pronounced vocal differences (investigated in Part I of this study). We further aimed to broaden the understanding of avian ecology and evolution in historically underrepresented regions because many of the species in our study occur exclusively in Central and South America (Nuñez et al 2021).…”
Section: Introductionmentioning
confidence: 86%
“…Additionally, we examined whether species living in closer proximity displayed greater color divergence as a test of the species recognition hypothesis. We predicted (1) plumage of both sexes would be largely driven by migration behavior, diet, climate, and habitat because these aspects have been found to influence coloration in other groups (e.g., Reudink et al 2015, Simpson et al 2015, Ward et al 2021, and (2) we would find less support for the species recognition hypothesis because many Tyrant flycatchers exhibit similar plumage within genera but display pronounced vocal differences (investigated in Part I of this study). We further aimed to broaden the understanding of avian ecology and evolution in historically underrepresented regions because many of the species in our study occur exclusively in Central and South America (Nuñez et al 2021).…”
Section: Introductionmentioning
confidence: 86%
“…We found that for most species analyzed (14 out of 18), age was an important driver of scaled mass index. Age-dependent responses to weather variables have been demonstrated previously via numerous pathways including differential migratory phenology (Jarjour et al, 2017), phenological (Bonamour et al, 2020) and phenotypic plasticity (Ward et al, 2021), and existing studies on body condition (Gardner et al, 2016(Gardner et al, , 2018McLean et al, 2018). A wide body of existing literature also suggests that body condition fluctuates as birds age (Angelier et al, 2011;Rockwell et al, 2012;Welcker et al, 2015), due in part to the fact that adult birds may outcompete juvenile birds for more limited resources in times of extreme weather (Rockwell et al, 2012).…”
Section: Age Effectsmentioning
confidence: 96%
“…Melanin‐based plumage in fox sparrows Passerella iliaca also changes colour over time (Weckstein et al 2002), possibly due to UV exposure or accumulation of dirt and oils on the feathers (Montgomerie 2006). Additionally, colour in many species changes with age – sometimes dramatically through delayed plumage maturation (Hawkins et al 2012) and sometimes more subtly as individuals age (Marini et al 2015, Ward et al 2021); therefore, it is important for studies to assess the environmental, biological, ontological and temporal influences on feather colour to help unravel the mechanisms regulating this phenotypic trait.…”
Section: Introductionmentioning
confidence: 99%